An analysis of the role played by decentralisation in promoting good governance in Africa: case of Zimbabwe 1990-2016 - Mazenge, Obedience (Midlands State University, 2018)
Governance in Africa has been since driven by poor policy formulation and lack of political will by leading officials. Decentralisation has mainly been used to bribe the masses given that African states are a product of colonialism and for redistribution of resources to mean equality in accessing them. African states has decentralised power of which decentralisation as a process suffered incompletion in practice. Since 1980 the government have been aiming at eradicating poverty through empowerment programmes that has also been part of the decentralization process. From 1990 to date Zimbabwe have faced an advantageous move in governance where new political parties came into existence, the legal framework have been changed to suit democratic or good governance demands through decentralization of which the process then faced challenges in proper implementation and political will.The researcher used Zimbabwe through the Masvingo city council to outline how decentralisation have affected good governance. The country is divided into ten provinces according to the 2013 constitution where the provinces are governed by local governments according to section 264. The local authorities have only managed to help counter the disadvantages set by the white regime or colonialists but have little or no power as they only enjoy delegated autonomy. Decentralisation has been used to regain political power evidenced by lack of participation of citizens and education concerning participation in policy formulation and access to information through the local authorities. Local authorities have tried to provide information to stakeholders and high levels of ill political will are being realised. The researcher has used qualitative research method so as to unearth the significance of decentralisation concerning good governance.